Perlindungan Dan Penghormatan Hak-Hak Masyarakat Hukum Adat Talang Mamak Atas Pengelolaan Sumber Daya Alam Di Kabupaten Tebo Provinsi Jambi - Pahlefi Pahlefi; Evalina Alissa (Recital Review, 2023)
This study aims to examine and analyze the urgency of respecting and protecting the right to manage natural resources for the Talang Mamak customary law community in Tebo District; and Researching and analyzing the conception of the relationship between the Talang Mamak people over natural resources in Tebo District. This research is an empirical research. The results of the study show that respect and protection of the right to manage the natural resources of the Talang Mamak customary law community in Tebo Regency have been carried out, although only in a number of sectors, namely recognition of existence in the government administration sector and residential areas. In the sector of recognition of the existence of customary law on natural resources by the Regional Government has not been carried out. Furthermore, the concept of the relationship between the Talang Mamak people over natural resources in Tebo Regency is a relationship concept based on political power and ideological power. Abstrak Penelitian ini bertujuan untuk Meneliti dan menganalisis urgensi penghormatan dan perlindungan hak mengelola sumber daya alam masyarakat hukum adat Suku Talang Mamak di Kabupaten Tebo; dan Meneliti dan menghanalisis konsepsi hubungan antara masyarakat suku Talang Mamak atas sumber daya alam di Kabupaten Tebo. Penelitian ini merupakan penelitian empiris. Hasil Penelitian menunjukkan bahwa penghormatan dan perlindungan hak mengelola sumber daya alam masyarakat hukum adat suku talang mamak di Kabupaten Tebo telah di lakukan walaupun hanya di sebagian sektot, yaitu pengakuan eksistensi di sektor adminitrasi pemerintahan, dan wilayah pemukiman. Disektor pengakuan terhadap eksistensi hukum adat terhadap sumber daya alam oleh Pemerintah Daerah belum di lakukan. Selanjutnya, Konsep hubungan antara masyarakat suku Talang Mamak atas sumber daya alam di Kabupaten Tebo adalah konsep hubungan berdasarkan kekuasaan politk dan kekuasaan ideologi.